Strategies for surviving: Using information / Mahizan Muhamad Isa and Nurul Alia Najwa Yahya - Muhamad Isa, Mahizan; Yahya, Nurul Alia Najwa (Faculty of Information Management, 2015)
The word information was derived from Latin "Informant" which means "give form to". Information can be defined as something about knowledge. It can be something about knowledge gained through study, communication, research and others else. As we all know, information is very important in our daily life. Without have enough information, we are nothing and nobody. The other meaning of information is it also known as stimuli that have to mean in some context for its receiver. When information is entered into and stored in a computer, it is generally referred as data. After processing, output data can again be perceived as information. Information also can be known as data that is accurate, and timely, specific and organized for a purpose, presented within a context, that gives it meaning and relevance, and can lead to increase in understanding and decreases in uncertainty. Information is valuable because it can affect behavior, decision, and outcome. When we talk about information, there are many definitions about it that we can simply understand.